2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.26999
|View full text |Cite
|
Sign up to set email alerts
|

The Prototype for X (PFX) Framework: Assessing Its Impact on Students' Prototyping Awareness

Abstract: Jessica Menold is a third-year graduate student interested in entrepreneurship and the design process. She is currently conducting her graduate research with Dr. Kathryn Jablokow and Dr. Timothy Simpson on a project devoted to understanding how prototyping processes affect product design. Jessica is interested in exploring how a structured prototyping methodology, Prototype for X, could increase the end design's desirability, feasibility, and viability. She is also working to understand how these methods affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Other research falls into the scope of evaluating structured methods and prototyping tools (Menold et al . 2016; Ramos & Wallace 2019; Menold et al . 2019); nevertheless, they do not explicitly study the purposes of prototyping.…”
Section: Research Aims and Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research falls into the scope of evaluating structured methods and prototyping tools (Menold et al . 2016; Ramos & Wallace 2019; Menold et al . 2019); nevertheless, they do not explicitly study the purposes of prototyping.…”
Section: Research Aims and Objectivesmentioning
confidence: 99%
“…Other student-based studies reinforce the above statement by concluding that the application of structured methods and supporting tools raises students’ overall prototyping awareness and therefore results in the delivery of higher quality prototypes (Menold et al . 2016; Ramos & Wallace 2019). Along with the input of students’ self-reported behaviour, researchers particularly note that the employment of such frameworks and support platforms enables students to broaden their prototyping scope and extend their focus on multiple design qualities rather than only on technical aspects (Menold et al .…”
Section: Introductionmentioning
confidence: 99%
“…Key findings indicate that prototypes with fewer parts result in better design outcomes and that the time spent on prototyping is not correlated with the project's success [7]. Another student-based study resulted in the confirmation that by applying structured methods for focused prototyping they managed to raise students' awareness and therefore facilitating them in creating better quality prototypes [14]. Students' use of prototypes has been also examined extensively through a comprehensive investigation of their prototyping activities using semistructured interviews.…”
Section: Studies In Students' Prototyping Activitiesmentioning
confidence: 99%
“…Structured prototyping methods can promote feelings of control and lead to an increase in creative output, higher levels of motivation, and advancement in the overall quality of design. [7] With regard to the use of rapid prototyping for design visualization and validation in a design course, it was found that having a physical three-dimensional model that can be seen, touched, and handled allows students to receive meaningful comments from peers, instructors, and potential end-users. [8] The relative speed and facility of the rapid prototyping process enables students to obtain prompt feedback on their designs and make revisions to improve them.…”
Section: Literature On Teaching Design and Prototypingmentioning
confidence: 99%